Molecular characterization and phylogenetic analysis tree of Shiga toxin-producing Escherichia coli (STEC) from local Basturma in Mosul city, Iraq - Yaman S. Fadhil; Ayman H. Taha; Omar H. Sheet (Iraqi Journal of Veterinary Sciences, 2025)
Escherichia coli (E. coli) stands out as the primary microorganism transmitted through food, having a variety of virulence factors, including uidA, Stx1, Stx2, and Rfb, which can cause food poisoning in people. One serotype of the bacterial species E. coli that is well-known for its capacity to generate a toxin similar to Shiga is E. coli O157:H7. It is a source of illness, frequently linked to foodborne infections brought on by consuming tainted and uncooked food, like raw milk and undercooked ground beef. Basturma is a traditional meat product crafted to preserve meat in Iraq. Forty-five samples of locally produced Basturma were collected from a variety of local stores across different regions in Mosul city, and the study period extended from April 2023 to June 2023. The results of our study showed that the classical microbiology methods and PCR methods concurred in identifying E. coli in local Basturma samples at a rate of 6 out of 45 (13.4%). All E. coli isolates were found to possess the specific-species uidA gene (100%), with a molecular weight of 623 bp. The PCR analysis further revealed that 1 out of 6 isolates (16.7%) carried the Stx1 gene with a molecular weight of 347 bp, while none of the E. coli isolates harbored the Stx2 and rfb genes. Not all isolates from Basturma were E. coli O157:H7. High similarity between E. coli isolated from Bab Al-Tob and Ras Al-Jada. Furthermore, the E. coli isolated showed a close relationship with E. coli isolated from different countries in the world.